2016
DOI: 10.1245/s10434-016-5197-0
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemoradiation Followed by Surgery for Locally Advanced Gallbladder Cancers: A New Paradigm

Abstract: Locally advanced unresectable cancers may benefit from neoadjuvant chemoradiation to facilitate a curative resection with a good survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 22 publications
0
36
0
Order By: Relevance
“…The heterogeneity in the data should be noted: the mix of symptomatic and incidental cancers; gallbladder and other extrahepatic cholangiocarcinomas, studies also including intrahepatic cholangiocarcinomas; the type and duration of chemotherapy used in various time intervals; and a selection bias for both surgery and adjuvant therapy in most of the reports. As the concept of neoadjuvant therapy is not possible, by definition, in incidental gallbladder cancers, and symptomatic cancers may have a different inherent biology, findings from the present data would need to be extrapolated. Consequently, guidelines and consensus statements are vague, but recommend adjuvant chemotherapy for most patients after resection, in particular those with any T2 disease and above with N1 disease, given the high risk of recurrence and nodal dissemination.…”
Section: Resultsmentioning
confidence: 97%
“…The heterogeneity in the data should be noted: the mix of symptomatic and incidental cancers; gallbladder and other extrahepatic cholangiocarcinomas, studies also including intrahepatic cholangiocarcinomas; the type and duration of chemotherapy used in various time intervals; and a selection bias for both surgery and adjuvant therapy in most of the reports. As the concept of neoadjuvant therapy is not possible, by definition, in incidental gallbladder cancers, and symptomatic cancers may have a different inherent biology, findings from the present data would need to be extrapolated. Consequently, guidelines and consensus statements are vague, but recommend adjuvant chemotherapy for most patients after resection, in particular those with any T2 disease and above with N1 disease, given the high risk of recurrence and nodal dissemination.…”
Section: Resultsmentioning
confidence: 97%
“…The role of chemoradiation in neo‐adjuvant setting has been reported only in two studies with one of them showing a potential detrimental effect . We have recently reported our experience of use of NACT/RT in 28 patients with a resectability rate of 56% and a 5‐year OS for 47% for patients undergoing resection . The twenty‐one patients who received NACT/RT in our series were a part of this study with similar outcomes.…”
Section: Discussionmentioning
confidence: 65%
“…Surgery was performed after 3‐4 cycles of chemotherapy comprising of gemcitabine/cisplatin or gemcitabine/oxaliplatin. Neo‐adjuvant chemoradiation (NACT/RT) using intensity‐modulated radiotherapy (IMRT) was administered as a part of an ongoing institutional review board approved phase II study . The dose to the gross tumor was 57 Gy over 25 fractions in 5 weeks, whereas the clinical target volume (CTV) received 45 Gy over 25 fractions.…”
Section: Methodsmentioning
confidence: 99%
“…However two recent studies; one from Tata memorial, Mumbai and another from SGPGI, Lucknow has shown that use of Neoadjuvant Chemoradiotherapy benefitted the locally advanced carcinoma gall bladder patients in facilitating the resectability rate with a chance of improved survival. 28,29 With the current approach of extended cholecystectomy and chemotherapy regimen it is unlikely that further improvement in survival will be achieved. Development of targeted agents based on understanding of molecular biology has the potential for further improvement in survival.…”
Section: Survival Functionsmentioning
confidence: 99%